2013
DOI: 10.5935/0101-2800.20130032
|View full text |Cite
|
Sign up to set email alerts
|

Immunosupressive therapy in children with steroid-resistant nephrotic syndrome: single center experience

Abstract: In our experience, treatment with MMF showed positive results such as decrease in the frequency of relapses, less proteinuria, and reduction in the dose of steroids administered without deterioration of glomerular filtration rates. However, more studies are needed to assess efficacy, safety, and optimal dosage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The present study reported an 80% remission rate for MMF combined with CsA and low-dose prednisone in 10 cases of SRNS, in whom CsA proved failure after three months. Similarly, a 70% remission rate was reported recently by Echeversi and colleagues ( 24 ). MMF is not recommended for sole use in steroid-resistant cases; it was reported to induce the reduction of proteinuria with partial remission ( 21 ).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The present study reported an 80% remission rate for MMF combined with CsA and low-dose prednisone in 10 cases of SRNS, in whom CsA proved failure after three months. Similarly, a 70% remission rate was reported recently by Echeversi and colleagues ( 24 ). MMF is not recommended for sole use in steroid-resistant cases; it was reported to induce the reduction of proteinuria with partial remission ( 21 ).…”
Section: Discussionsupporting
confidence: 81%
“…More recent studies have reported positive results with decrease in relapse rate, less proteinuria, and steroid-sparing dose without any nephrotoxic effect. It was approved by FDA in 1995 for use in pediatric renal transplantation, SRNS, and SDNS ( 24 , 26 ). CPO was used more commonly in the SRNS group (68.6%), mainly as a first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age at first attack in this study ranged from 3 to 11 years with median of 9 years and mean of 5.30 ± 2.45. On the contrary, Echeverri et al, [20] reported a lower age at first attack which ranged from 7 months to 16 years, with median of 25 months. This difference between studies may be due to different ethnic group.…”
Section: Resultsmentioning
confidence: 92%
“…MMF is reported to induce the reduction of proteinuria with partial remission (23). However, some studies have reported positive results with decrease in relapse rate, less proteinuria, and steroid sparing dose without any nephrotoxic effect (24,25). Due to lack of side effects such as liver and kidney toxicity and myelosuppression, MMF has become a commonly used immunosuppressant, but the study results are variable with regard to its efficacy in SRNS children (16).…”
Section: Discussionmentioning
confidence: 99%